تنمية وتثمين الموارد العلفية المحلية بولاية قبلي - البدائل والإمكانيات والتصنيع (مخلفات النخيل نموذجا) - Moujahed, Nizar; Mannai, Amal (National Agronomic Institute of Tunisia, 2023)
Oral presentation on the topic "Alternatives, Potentials, and Manufacturing - A Case Study of Palm Residue" delivered during the regional workshop on "the development and valorization of local forage resources in the Kebili governorate," held on May 25 and 26 in Kebili, Tunisia.